Além das Armas: Guerrilheiros de Esquerda no Ceará durante a Ditadura Militar - Farias, José Airton de (2007)
The present work has as object the guerrilla fighters of left – mainly of the ALN (National Liberating Action) and the PCBR (Communist Revolutionary Brazilian Party) – in the state of Ceará during the military dictatorship, necessarily between 1968 and 1972. It interprets its trajectories and experiences, as they had been changing with the increase of the repression on the part of the existing authoritarian regimen in Brazil since 1964. By means of analysis of interviews, official periodicals and documents, it equally tries to understand the bonding between the model of solidarity and the yearning of militants for a fair society with old traditions, mostly of the Jewish-Christian culture, without discarding the direct influences of family, friends, the school’s space, the Catholic Church and Nationalism. It also studies the context in which the guerrilla occurred and the main actions of the revolutionaries in the state.